2005
DOI: 10.1105/tpc.105.033738
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis CYP85A2, a Cytochrome P450, Mediates the Baeyer-Villiger Oxidation of Castasterone to Brassinolide in Brassinosteroid Biosynthesis

Abstract: The conversion of castasterone (CS) to brassinolide (BL), a Baeyer-Villiger oxidation, represents the final and rate-limiting step in the biosynthesis of BL in plants. Heterologously expressed Arabidopsis thaliana CYP85A2 in yeast mediated the conversion of CS to BL as well as the C-6 oxidation of brassinosteroids (BRs). This indicated that CYP85A2 is a bifunctional enzyme that possesses BR C-6 oxidase and BL synthase activity. CYP85A2 is thus a cytochrome P450 that mediates Baeyer-Villiger oxidation in plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
220
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 241 publications
(230 citation statements)
references
References 53 publications
6
220
1
3
Order By: Relevance
“…This gene encodes a BR C-6 oxidase catalyzing the last conversion steps of BL synthesis in Arabidopsis (Kim et al, 2005;Nomura et al, 2005), and its organ-specific expression pattern has been shown to be similar to that of CPD (Bancos et al, 2002;Castle et al, 2005). Although the luminescence emitted by CYP85A2:LUC transgenic seedlings was about 10-fold lower than that of the CPD:LUC-carrying ones, it also exhibited a diurnal profile with maxima and minima at similar time points as seen in the case of CPD (Fig.…”
Section: Diurnal Changes In the Expression Of Br-biosynthetic Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…This gene encodes a BR C-6 oxidase catalyzing the last conversion steps of BL synthesis in Arabidopsis (Kim et al, 2005;Nomura et al, 2005), and its organ-specific expression pattern has been shown to be similar to that of CPD (Bancos et al, 2002;Castle et al, 2005). Although the luminescence emitted by CYP85A2:LUC transgenic seedlings was about 10-fold lower than that of the CPD:LUC-carrying ones, it also exhibited a diurnal profile with maxima and minima at similar time points as seen in the case of CPD (Fig.…”
Section: Diurnal Changes In the Expression Of Br-biosynthetic Genesmentioning
confidence: 99%
“…In Arabidopsis, C-6 oxidation is catalyzed by two enzymes, CYP85A1 and CYP85A2, of partially redundant functions. Under in vitro conditions, yeastexpressed CYP85A1 was shown to generate teasterone, typhasterol, and bioactive castasterone from their respective 6-deoxo precursors, whereas CYP85A2, in addition to these reactions, also catalyzed the BaeyerVilliger oxidation of castasterone to BL (Shimada et al, 2001Kim et al, 2005;Nomura et al, 2005). The C-22 and C-23 hydroxylation reactions were found to be mediated by DWF4/CYP90B1 and CPD/CYP90A1, respectively (Szekeres et al, 1996;Choe et al, 1998).…”
mentioning
confidence: 99%
“…In Arabidopsis thaliana, two orthologs of tomato CYP85, designated as CYP85A1 and CYP85A2 have been identified. 3 Molecular genetic and biochemical analysis of CYP85A1 and CYP85A2 revealed that CYP85A1 is a BR Notes 6-oxidase, and CYP85A2 is a bi-functional enzyme whose activity is not only BR 6-oxidase but also brassinolide (BL) synthase which catalyze the conversion of CS to BL, the last step of C28-BRs biosynthesis. Recently, the same bi-functional enzyme as CYP85A2, designated as CYP85A3, has been characterized in tomato fruit.…”
Section: Compoundmentioning
confidence: 99%
“…After reversed-phase HPLC (Senshu-Pak Pegasil-B, 4.6 × 250 mm), the fractions corresponding to authentic 6-oxoCHN (18 -19 min) and cholest-4-en-3-one (37 -39 min) were collected, and then analyzed via capillary GC-MS. 3 After 30 minutes of treatment of N-methyl-N-TMS-trifluroacetamide at 70 o C, trimethylsillylic (TMSi) ether of a compound in HPLC fractions 18 and 19 yielded a molecular ion at m/z 474 and prominent ions at m/z 459, 445, 384, 221 and 159 at the same GC retention time (19.51 min) as that of authentic 6-oxoCHN TMSi ether (Table 1). Therefore, the compound was identified as 6-oxoCHN.…”
mentioning
confidence: 99%
See 1 more Smart Citation